Conventional and new materials for Selective Catalytic Reduction (SCR) of NOx - Liu, Yu (2020)
It is important and necessary to minimize NOx pollutant released into the atmosphere owing to the harmful environmental and health effects brought by NOx emission. Many techniques are available to reduce NOx emission, among of them, Selective Catalytic Reduction (SCR) is considered as one of the most efficient techniques. Conventional SCR systems involve ammonia (NH3) or urea (CO(NH2)2) as a reducing reagent to reduce NOx to N2 and H2O at high temperatures 300–400 °C. Research on developing novel low‐temperature catalysts (LTC) for SCR of NOx still remains of interest. This work reviewed and compared conventional SCR catalysts with newly emerging Metal‐Organic‐Frame (MOFs) materials as potential alternatives for SCR catalysts.